Teaching reading comprehension through SMART strategy to the tenth graders of vocational high school - Meilinda Astuti; Dewi Syafitri; Agus Triyogo (Journal of English Language and Pedagogy, 2020)
The objective of this research was to find out whether or not it was significantly effective to teach reading comprehension through self-monitoring approach to reading and thinking (SMART) strategy to the tenth-grade students of SMK Pertanian Negeri 2 Tugumulyo. The method applied in this research was quantitative with the pre-experimental method. The total number of population was 130 students of the tenth-grade students of SMK Pertanian Negeri 2 Tugumulyo. The sample of this research had taken by using cluster random sampling. The number of the sample was 33 students of class X.2. The instrument of the research was in form of multiple-choice tests. The data were analyzed through four techniques: individual score, conversion based on minimum mastery criteria (MMC), normality testing, and paired t-test. Based on the result of data analysis, the writers found that there were: the students’ average score in the pre-test was 58.18 and the post-test was 76.36, normality testing in the pre-test was 2.0724 and the post-test was 4.471, and the result of paired t-test was 6.401, which was higher than 1.697 with 95% (0.05) significance level for one tailed-test. It means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. In conclusion, it was significantly effective to teach reading comprehension through Self-monitoring approach to reading and thinking (SMART) strategy to tenth-grade students of SMK Pertanian Negeri 2 Tugumulyo.